Staf Pastoral Sebagai Koordinator Pembangunan Iman Anak-Anak di St. Stasiun Francis Assisi, St. Paroki Perdamaian Maria Ratu Nehas - Johanes Adrian; Carmelo Cedric (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to accompaniment animator coaching fith cild in station parish st. maria queen peace nehas liah bing. Trough this study on expect pastoral works to assits children with who is full of spirit so as to attract theinterest of children for follow the activity of coaching fait. This type of research is motor and documentation research rurites include convestation with informant profile informant determination theme. Possibili will accur and qualitative. Date obtained by obsevasi, intview motor has played and active role in the activities of coaching development of children but the curry. From the result of research showed that pastoral officers as many volunteers and do not get choaching an fith to the children. So they can grow up and which is special so as to result in less in mentor mentoring the conclusiob of this research is a very in a the chaperone of the builder involve yourself to be successor of the church that people hoper for.